Tomato plant inheritance of antixenotic resistance to tomato leafminer - Antônio, Adilson de Castro; Silva, Derly José Henriques da; Picanço, Marcelo Coutinho; Santos, Nerilson Terra; Fernandes, Maria Elisa de Sena (Pesquisa Agropecuária Brasileira, 2013)
The objective of this work was to determine the inheritance of resistance by antixenosis in tomato plants (Lycopersicon esculentum) to tomato leafminer [Tuta absoluta (Lepidoptera: Gelechiidae)]. Evaluations were performed for tomato plants of the generations P1, P2, F1, F2, RC1 and RC2. The measured characteristic in the parents, BGH-1497 (P2 male) and 'Santa Clara' (P1 female), and in the F1, F2, RC1 and RC2 generations was the number of eggs per plant. This number was converted to the oviposition nonpreference index. The inheritance of antixenosis resistance of genotype BGH-1497 is ruled by a gene of greater effect and polygenes in epistatic interactions, with a phenotypic proportion of 13:3 between susceptible and resistant genotypes, respectively.

O objetivo deste trabalho foi determinar a herança da resistência por antixenose em plantas de tomate (Lycopersicon esculentum) à traça-do-tomateiro [Tuta absoluta (Lepidoptera: Gelechiidae)]. As avaliações foram realizadas em plantas de tomate das gerações P1, P2, F1, F2, RC1 e RC2. A característica medida nos pais, BGH-1497 (masculino P2) e 'Santa Clara' (feminino P1), e nas gerações F1, F2, RC1 e RC2 foi o número de ovos por planta. Este número foi transformado em índice de não preferência por oviposição. A herança da resistência por antixenose do genótipo BGH-1497 é governada por um gene de efeito maior e poligenes em interações epistáticas, com uma proporção fenotípica de 13:3 entre genótipos suscetíveis e resistentes, respectivamente.
Keywords: Lycopersicon esculentum; Tuta absoluta; Genetic resources